LIRA IMANENTE: POEMA SUJO & METAFORMOSE - MOREIRA, Wilton Cardoso (2009)
The present paper is a reading of Poema Sujo (1991) by Ferreira Gullar and Metaformose (1998) by Paulo Leminski, trying to establish how those poems, even having absorbed procedures from modernism on their writing, in fact move away from the poetry of modernism, once by the so called lyricism of content, of subjective expression or social representation, either of the objective lira that tries to build the poem as an autonomous structure of language, a trend that gets from the concretism its more important development. The objective is to show that Poema Sujo and Metaformose are included under the regimen of another lira or poetry and are conceived as works that can not be reduced or explained by any fundament, essence or structure of base, even on its more empirical or historical meanings, such as the subjectivity, the society and the language bases that the theories, critical readings and poetry of modernist nature use to prescribe for the creation and interpretation of the poem. Both poems are not possible to be not interpreted nor even as hybridism or synthesis of two or more of these fundamentals. They are poems that refuse the fundamentals transcendence and as a consequence are marked as an immanent lira. Another proposal of this paper is to show as this immanent lira get close to the ideas of some European thinkers contemporaries of Gullar and Leminski, particularly Jacques Derrida, Gilles Deleuze & Felix Guattari and Gianni Vattimo, whom looked to develop a Philosophy that needs the notions of be, fundamentals, essence and unit. The final part of this thesis is an attempt of elaboration with a bit more severity the concept of immanent lira in contrast with the poetical of modernity and modernism; and relate them to the problematic concepts of post-modernity and post-modernism; and to outline some problems that the concept and practice of a lyricism (and a literature) immanent bring to the contemporary literature